Rapid Determination of Iron in Water by Modified Thiocyanate Method - Goswami, D. C.; Kalita, H. (Defence Science Journal, 2013)
A rapid spectrophotometric method for determination of iron in water by oxidising ferrous iron with ceric ammonium sulphate at roomtemperature followed by formation of ferric thiocyanate colour complexwith potassium thiocyanate has been described. The method is simple and rapid as compared to other standard methods used in water analysis and iron content of water upto 5 ppm can be determined by this method with a maximum error of 2.8 per cent